The effect of a coaching program on asthma control and health care utilization in children with asthma. (1st February 2021) - Horwitz, Dana; Kestenbom, Inbal; Goldbart, Aviv; Chechik, Tzila; Dizitzer, Yotam; Golan-Tripto, Inbal
ABSRACT: Objective : Poor adherence to asthma therapy is a major problem in the management of asthma. We aimed to assess if a designed coaching program in children with asthma, coming from low socioeconomic background, will reduce respiratory morbidity and health care utilization. Methods : A prospective interventional pilot study enrolling children aged 3–18 years, admitted to Soroka University Medical Center (SUMC) between October 2015 and May 2016 due to asthma exacerbation. The intervention group was part of a coaching program, which was conducted by medical and paramedical personnel and included a diagnostic and personal educational office visit and a house visit by a nurse educator for asthma. The control group comprised of demographically matched children with asthma, who were admitted to the SUMC, but did not go through any intervention. Medications purchase and health care utilization were extracted from the participants' HMO databases, during 1-year of follow-up. Results : 41 children were enrolled to the intervention group, with 63 children as a control group. No differences were found in asthma-related drugs purchase, number of clinic visits, ER admissions and hospitalizations during the follow-up year, although the intervention group showed a trend towards having a shorter length of stay (2.3 vs. 4.5 days, Cohen's D = 0.44, p = 0.06). The intervention group demonstrated subjective improvement in asthma control, as reflected in Asthma Control Test questionnaires. Conclusions : In this pilot study of coaching program for children with asthma coming from low income families, no decrease in health care utilization was shown. Larger and longer intervention programs are needed.